Pelatihan Pengolahan Buah Naga di Desa Grajagan Sebagai Alternatif untuk Meningkatkan Penghasilan Rumah Tangga - Harliwanti Prisilia; Dimas Aji Purnomo; Heri Sujatmiko (Abdi Panca Marga, 2021)
ABSTRACT Dragon fruit is a very popular fruit among farmers in the southern Banyuwangi area, especially in Grajagan village, Purwoharjo district. One of the obstacles faced by dragon fruit farmers is that at the time of the dragon fruit harvest, prices tend to drop drastically due to the large supply of dragon fruit being harvested. The objectives of this community service activity are as follows, namely providing alternative dragon fruit processing technology, providing alternative dragon fruit processed products to consumers in the form of dragon fruit syrup and jam and providing an entrepreneurial spirit by providing skills that are in accordance with the potential of existing raw materials, namely dragon fruit. For service partners, namely housewives. The implementation method is by providing direct training on how to process dragon fruit. Keywords: dragon fruit, Grajagan village, entrepreneur